Wpływ Więzów Geometrycznych I Dynamicznych Na Obszary Rezonansowe w Zagadnieniu Stateczności Dynamicznej Pręta Cienkościennego O Profilu Otwartym - Piszczek, K. (Engineering Transactions, 1957)
This paper seeks to determine the influence of the constraints referred to in the title on the dynamical stability of a straight thin-walled bar with hinged support end conditions. The problem is solved on the assumption of existence of a singIe symmetry axis of the cross-section, the force acting at an arbitrary point of that axis. The method of solution is based on Ref. [2] which is shown to be applicable to this problem. However, the method used in the present paper, seems to be more clear than that of Ref. [3]. The influence of rotation of the cross-sections is also taken into consideration. The notion of the geometrical and dynamical constraint is introduced. By geometrical constraint, we understand a conjugation concerning the geometry of the cross-section, the dynamical constraint being connected with the attachment point of the force. It is shown that the condition of existence of the most narrow resonance region is A2 = 0 where Ag denotes the expression (3.1).